Medical stratification in Vietnam (Medicine Anthropology Theory, 2014)
Market transition in Vietnam is known to have fueled health disparities, but racialized and nationality-linked aspects of the country’s medical stratification have received less attention, despite the growing presence of foreigners using the health system. Field experiences reveal the country’s increasing health and medical inequity – legible in the social, linguistic, economic, and physical distinctions between public health stations staffed by government employees and the private clinics serving mostly expatriates. Ethnographic interviews and experiences of receiving care in both public and private facilities inform my argument that the privatization of Vietnam’s health sector produces racialized, classed, and citizenship-linked forms of medical profit, privilege, segregation, and risk – trends visible both in recent debates over US health policy and recent episodes of pandemic disease outbreak.